Stamps on the amphoras of Thasos: circulation, production and connection in the Mediterranean - Porto, Vagner Carvalheiro; Hora, Juliana Figueira da (Romanitas - Revista de Estudos Grecolatinos, 2016)
This article aims to present and discuss the production and circulation of Thasian amphora stamps. We try to show the importance of Thasos in the context of amphora’s production in the Aegean, the history of this island within Aegean, Mediterranean and Black Sea trade networks. Finally, we try to demonstrate some relationships concerning new theoretical proposals related to connectivity of the Mediterranean and the network of relations between the inhabitants of these regions in Antiquity.